Electronic conductive and corrosion mechanisms of dual nanostructure CuCr-doped hydrogenated carbon films for SS316L bipolar plates. (August 2021) - Jia, Q.; Mu, Z.; Zhang, X.; Zhang, B.; Liu, R.; Gao, K.; Yu, Y.; Lai, Z.; Zhang, J.
Abstract: The carbon-coated metal bipolar plate is believed to be a potential substitute of the traditional graphite bipolar plate. However, instead of pyrolytic graphite, carbon films grown by using hydrocarbon as the carbon source have a higher deposition rate but lower conductivity. Aiming to resolve this complaint, here, a new strategy of in-situ catalytic decomposition of methane via reactive magnetron sputtering of a Cr0.6 Cu0.4 target in methane and argon atmosphere was proposed without heating. A dual structure C18.6 Cr0.06 Cu (S65) film with graphene-like carbon bridged nano-Cu clusters within amorphous carbon clusters embedded, which has a deposition rate (~24.1 nm/min) about four times higher than other reports (≤6.2 nm/min), with the interface contact resistance of 7.34 mΩ cm 2 . The distinct mechanisms of good conductive and anti-corrosion can be understood as (1) the bridged nano-Cu clusters and graphene-like carbon structures construct an interconnected network in the bulk S65 film, endowing the S65 good conductivity, (2) the nano-Cu clusters are isolated by the graphene-like carbon structures and amorphous carbon clusters, which protect the nano-Cu clusters un-contacting with the corrosive medium, bringing the S65 excellent anti-corrosion properties. Our work opens a new route for the rapid deposition of carbon film for bipolar plate application. Highlights: It is the first time to deposited CxCryCu film via in-situ catalytic decomposition ofw methane. The Cx Cry Cu films with excellent conductivity and corrosion resistance. Nano-Cu clusters and graphene-like carbon structures construct an interconnected space network that brings good conductivity. Bridging nano-Cu clusters are isolated by graphene-like carbon structures and amorphous carbon clusters, bringing excellent corrosion resistance.